2020
DOI: 10.1007/s00339-020-03913-8
|View full text |Cite
|
Sign up to set email alerts
|

Extreme biomineralization: the case of the hypermineralized ear bone of gray whale (Eschrichtius robustus)

Abstract: Selected hypermineralized bones (rostrum and tympanic bullae) have yet to be characterized for diverse species of whales (Cetacea). Hypermineralization in these structures is an example of extreme biomineralization that, however, occurs at temperatures around 36 °C. In this study we present the results of analytical investigations of the specimen of tympanic bulla isolated from gray whale (Eschrichtius robustus) for the first time. Examination of the internal surface of the bone mechanically crushed under a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 74 publications
0
17
0
Order By: Relevance
“… 62 Furthermore, there are pathways that are specific to one process, such as bone elongation in the growth plate, or pathways that are responsible for producing hyper-mineralized bones. 63 It is therefore challenging to identify common underlying ion pathways in bone formation.…”
Section: Test Casesmentioning
confidence: 99%
See 1 more Smart Citation
“… 62 Furthermore, there are pathways that are specific to one process, such as bone elongation in the growth plate, or pathways that are responsible for producing hyper-mineralized bones. 63 It is therefore challenging to identify common underlying ion pathways in bone formation.…”
Section: Test Casesmentioning
confidence: 99%
“…The complexity may also be a strategy that is tailored to meet different requirements, such as rapid surface thickening of bone, especially during early development, versus maintenance of mature bone by remodeling . Furthermore, there are pathways that are specific to one process, such as bone elongation in the growth plate, or pathways that are responsible for producing hyper-mineralized bones . It is therefore challenging to identify common underlying ion pathways in bone formation.…”
Section: Test Casesmentioning
confidence: 99%
“…9 CaCO 3 is also synthesized by bacteria, 10 even in extreme biomineralization conditions, 11 and is an essential component of mineralized tissues as in the apatitic whale bone. 12,13 Crystalline CaCO 3 exhibits three polymorphs: hexagonal vaterite, orthorhombic aragonite, and rhombohedral calcite, in order of increasing thermodynamic stability. 14 Two hydrated crystal phases of CaCO 3 , monohydrocalcite (CaCO 3 ÁH 2 O) and ikaite (CaCO 3 Á6H 2 O), have been known for more than a century, while recently, hemihydrate CaCO 3 Á 1 2 H 2 O with a monoclinic structure has been discovered.…”
Section: Introductionmentioning
confidence: 99%
“…Our review of numerous recent scientific publications on biomineralization has revealed emphasis of the overall scientific attention towards calcification [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ], biosilicification [ 14 , 15 , 16 ], biomagnetism [ 17 , 18 ], and multiphase biomineralization [ 19 , 20 , 21 , 22 , 23 ]. Traditional objects of study continue to include molluscs [ 24 , 25 , 26 , 27 , 28 ], sea urchins [ 29 ], and skeletal structures such as eggshells [ 30 ], teeth [ 31 , 32 ], and bones [ 33 , 34 , 35 , 36 ]. While it is understandable to focus on the biomineralizing organisms typically encountered by humans on Earth, this focus tends to overlook a variety of distinct biomineralization pathways seen in extremophiles.…”
Section: Introductionmentioning
confidence: 99%